TELEVISI KOMUNITAS DITENGAH EKSISTENSI YANG BERMASALAH - Reza Aprianti (Wardah, 2012)
Television community group of individuals born from the desire to have a container that is expected to accommodate their needs based on common interests, geography, identity, culture, interests. In order to maintain its existence, community television is not uncommon to have to deal with a variety of problems, both in terms of lack of clarity in regulation, lack of funds, poor managerial and organizational mistakes in establishment  commercial television stations, sometimes leading to the independence of betting or even stopping the operation of the media.